2021
DOI: 10.1002/jrs.6144
|View full text |Cite
|
Sign up to set email alerts
|

Detecting pigments from gypsum endoliths using Raman spectroscopy: From field prospection to laboratory studies

Abstract: Microbial colonisations of gypsum from different sites from Southern Sicily and Eastern Poland were investigated using laboratory-based Raman microspectrometers and portable Raman spectrometric devices. Selected zones of microbial colonisations of few types of gypsum are described from the point of view of the presence of algae and cyanobacteria. Macrocrystalline gypsum layers in Sicily and Eastern Poland originate from Tertiary sedimentary series. In Southern Sicily gypsum outcrops from late Miocene age were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 95 publications
(194 reference statements)
0
10
0
Order By: Relevance
“…In the first study, mostly green and brown areas of the layered systems were investigated and Raman features documented the presence of chlorophyll (especially common in green), carotenoids (found in all the coloured zones), scytonemin (encountered in the dark zones) and also phycobiliproteins. More detail on the distribution of carotenoids was recently collected [53] on endoliths from Southern Sicily, and three newly observed sites of cyanobacterial colonization in large gypsum crystals in Eastern Poland were included. Raman spectra document the presence of different carotenoids in the samples, with their highest amount being found in the brick-coloured strata corresponding to β-carotene exclusively, in the case of samples colonized by the filamentous green alga Trentepohlia at Chotel Czerwony.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, mostly green and brown areas of the layered systems were investigated and Raman features documented the presence of chlorophyll (especially common in green), carotenoids (found in all the coloured zones), scytonemin (encountered in the dark zones) and also phycobiliproteins. More detail on the distribution of carotenoids was recently collected [53] on endoliths from Southern Sicily, and three newly observed sites of cyanobacterial colonization in large gypsum crystals in Eastern Poland were included. Raman spectra document the presence of different carotenoids in the samples, with their highest amount being found in the brick-coloured strata corresponding to β-carotene exclusively, in the case of samples colonized by the filamentous green alga Trentepohlia at Chotel Czerwony.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the study of the biocolonization of minerals and rocky areas has taken on great importance, both in the area of art and archaeology, as well as in issues related to the possible presence of life on other planets. For example, Němečková et al [ 24 ] investigated microbial colonizations of gypsum from different sites from Southern Sicily and Eastern Poland using laboratory‐based Raman micro‐spectrometers and portable Raman spectrometric devices. Authors describe selected zones of microbial colonizations of few types of gypsum from the point of view of the presence of algae and cyanobacteria.…”
Section: Biocolonizations Of Mineralsmentioning
confidence: 99%
“…[ 46 ] More achievements of the technique appeared later on photosynthetic and protective pigments of very different microorganisms, including extremophillic ones, as reviewed, for example, by Jehlička et al and Maia et al [ 47,48 ] Raman spectroscopy was suggested as an excellent tool to rapidly prospect, detect and discriminate pigments on rocky outcrops. [ 49,50 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 57 ] They are also common photosynthetic pigments connected to the cyanobacterial endolithic colonisations at different sites in eastern Poland as reported recently. [ 50 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation